Relationship Between Perceived Parental Academic Expectations and Students' Self-Regulated Learning Ability: A Cross-Sectional Study - Xu, Ling; Ma, Lijun; Duan, Peng (Frontiers in Psychology, 2022)
In the field of self-regulated learning ability for college students, prior research usually neglected the role of parents when considering the physical distance between college and home. Indeed, an underlying describable driving force of learning remains embedded in the relationship between parents and students, even at the college stage. This study aimed to explore the relationships among perceived parental academic expectation, mastery goal orientation, self-reflection, and self-regulated learning ability of college students. Mediation and moderated mediation analyses were employed to analyze a sample of 691 college students. The results indicate that mastery goal orientation partially mediates the relationship between perceived parental academic expectation and self-regulated learning. In addition, self-reflection moderates the relationship between perceived parental academic expectation and self-regulated learning. The positive correlation between perceived parental academic expectation and self-regulated learning is stronger for the students with low level self-reflection than those with high level self-reflection.